Longitudinal characterization reveals behavioral impairments in aged APP knock in mouse models - Lisa Blackmer-Raynolds; Lyndsey D. Lipson; Isabel Fraccaroli; Ian N. Krout; Jianjun Chang; Timothy Robert Sampson (Scientific Reports)
Abstract APP knock-in (KI) mice serve as an exciting new model system to understand amyloid beta (Aβ) pathology, overcoming many of the limitations of previous overexpression-based model systems. The APPSAA mouse model (containing the humanized APP with three familial Alzheimer’s disease mutations) and the APPWT control (containing wildtype humanized APP) are the first commercially available APP KI mice within the United States. While APPSAA mice have been shown to develop progressive Aβ pathology and neuroinflammation, the age at which behavioral and cognitive impairments begin to develop has yet to be described. Therefore, we performed an in-depth longitudinal study over 16 months, assessing cognition in these two strains, as well as assessments of motor function. While no cognitive deficits are observed in either genotype throughout the first year of life, 16-month-old APPSAA, but not APPWT mice show initial signs of spatial memory decline. In addition, both genotypes display impaired motor function at the same age. Together, this data identifies a timeframe where behavioral deficits appear, providing an essential foundation for future studies using these model systems.